Current research status of third-generation sequencing technology in thalassemia detection - Zhu, Fenglin; Lai, Yunli; He, Sheng (Frontiers in Pediatrics, 2026)
Thalassemia is a hereditary hemolytic disorder primarily caused by defects in the hemoglobin genes, which impede the synthesis of hemoglobin peptide chains. This disease is mainly classified into two types: α and β. Currently, there is no effective treatment available that can completely cure this disease. The conventional screening techniques for thalassemia currently used in clinical practice have significant shortcomings, posing risks of missed diagnoses and misdiagnoses. As a molecular detection technology that has emerged in recent years, third-generation sequencing can specifically address the shortcomings of conventional detection methods, enhance the positive detection rate for novel thalassemia variants, and demonstrate broad application prospects. However, it remains in the stage of technical exploration and refinement. This review aims to systematically organize and thoroughly analyze relevant research literature on the application of third-generation sequencing technology in thalassemia detection. It seeks to comprehensively understand the current status of utilization of this technology in thalassemia research, thereby fully leveraging its technical advantages to support the prevention, control, and management of thalassemia.